Blocking nuclear export of HSPA8 after heat shock stress severely alters cell survival. Issue 1 (December 2018) - Wang, Fengjuan; Bonam, Srinivasa; Schall, Nicolas; Kuhn, Lauriane; Hammann, Philippe; Chaloin, Olivier; Madinier, Jean-Baptiste; Briand, Jean-Paul; Page, Nicolas; Muller, Sylviane
Abstract The nuclear translocation of endogenous heat shock cognate protein HSPA8 is a requisite for cell survival during oxidative and heat shock stress. Upon these events, cytoplasmic HSPA8 is thought to concentrate within the nucleus and nucleolus. When the situation returns to normal, HSPA8 is released from its nuclear/nucleolar anchors and redistributes into the cytoplasm. By using different stress conditions and a 21-mer phosphopeptide tool called P140, which binds HSPA8 and hampers its chaperone properties, we deciphered the cellular and molecular effects arising during this vital cytoplasmic-nuclear-cytoplasmic shuttling process. Using the non-metastatic fibroblastoid cell line MRL/N-1 derived from a MRL/MpTn-gld/gld lupus-prone mouse, we discovered that P140 treatment neutralized the egress of HSPA8 from nucleus to cytoplasm in the cell recovery phase. This lack of relocation of HSPA8 into the cytoplasm of heat-shocked MRL/N-1 cells altered the ability of these cells to survive when a second mild oxidative stress mimicking inflammatory conditions was applied. Crosslinking experiments followed by proteomics studies showed that P140 binds regions close to nuclear import and export signal sequences encompassed within the HSPA8 structure. These data are consistent with HSPA8 having a crucial cell protective role against reactive oxygen species (ROS) production by mitochondria during inflammatory conditions.